Bacteriophage PRD1 as a nanoscaffold for drug loading. Issue 47 (1st December 2021) - Duyvesteyn, Helen M. E.; Santos-Pérez, Isaac; Peccati, Francesca; Martinez-Castillo, Ane; Walter, Thomas S.; Reguera, David; Goñi, Felix M.; Jiménez-Osés, Gonzalo; Oksanen, Hanna M.; Stuart, David I.; Abrescia, Nicola G. A.
Abstract : Viruses are very attractive biomaterials owing to their capability as nanocarriers of genetic material. Abstract : Viruses are very attractive biomaterials owing to their capability as nanocarriers of genetic material. Efforts have been made to functionalize self-assembling viral protein capsids on their exterior or interior to selectively take up different payloads. PRD1 is a double-stranded DNA bacteriophage comprising an icosahedral protein outer capsid and an inner lipidic vesicle. Here, we report the three-dimensional structure of PRD1 in complex with the antipsychotic drug chlorpromazine (CPZ) by cryo-electron microscopy. We show that the jellyrolls of the viral major capsid protein P3, protruding outwards from the capsid shell, serve as scaffolds for loading heterocyclic CPZ molecules. Additional X-ray studies and molecular dynamics simulations show the binding modes and organization of CPZ molecules when complexed with P3 only and onto the virion surface. Collectively, we provide a proof of concept for the possible use of the lattice-like organisation and the quasi-symmetric morphology of virus capsomers for loading heterocyclic drugs with defined properties.